The journey metaphor in Brexit-related political cartoons. (October 2019) - Silaški, Nadežda; Đurović, Tatjana
Abstract: Against the backdrop of two theoretical frameworks, Critical Metaphor Analysis (Charteris-Black, 2004; Musolff, 2006, 2016, 2017) and multimodality from a cognitive viewpoint (Bounegru and Forceville, 2011; Forceville, 1996, 2008; Forceville and Urios-Aparisi, 2009; etc.), in this paper we address the topic of Brexit unfolded in pictorial and multimodal discourse in media in order to explore how this topic is communicated via metaphors in political cartoons. Our analysis focuses on the journey metaphor scenario, one of the most pervasive metaphor scenarios in Brexit-related political cartoons, particularly emphasising one of its structural elements, namely the means of transportation. The data collection for the analysis consists of 48 cartoons contained in a video clip named 100 Best Brexit Cartoons, made available on YouTube five days after the EU membership referendum took place in the UK. Our aim is twofold: to show how the means of transportation metaphor scenario is used to simplify and facilitate the understanding of the complex relations between Britain and the EU at a critical point in their history as well as how the use of the journey metaphor scenario in multimodal discourse becomes a powerful tool for conveying evaluative content when set within a specific socio-political context.